National Trends and Disparities in Hospitalization for Acute Hypertension Among Medicare Beneficiaries (1999–2019). Issue 21 (23rd November 2021) - Lu, Yuan; Wang, Yun; Spatz, Erica S.; Onuma, Oyere; Nasir, Khurram; Rodriguez, Fatima; Watson, Karol E.; Krumholz, Harlan M.
Abstract : Background: In the past 2 decades, hypertension control in the US population has not improved and there are widening disparities. Little is known about progress in reducing hospitalizations for acute hypertension. Methods: We conducted serial cross-sectional analysis of Medicare fee-for-service beneficiaries age 65 years or older between 1999 and 2019 using Medicare denominator and inpatient files. We evaluated trends in national hospitalization rates for acute hypertension overall and by demographic and geographical subgroups. We identified all beneficiaries admitted with a primary discharge diagnosis of acute hypertension on the basis of International Classification of Diseases codes. We then used a mixed effects model with a Poisson link function and state-specific random intercepts, adjusting for age, sex, race and ethnicity, and dual-eligible status, to evaluate trends in hospitalizations. Results: The sample consisted of 397 238 individual Medicare fee-for-service beneficiaries. From 1999 through 2019, the annual hospitalization rates for acute hypertension increased significantly, from 51.5 to 125.9 per 100 000 beneficiary-years; the absolute increase was most pronounced among the following subgroups: adults ≥85 years (66.8–274.1), females (64.9–160.1), Black people (144.4–369.5), and Medicare/Medicaid insured (dual-eligible, 93.1–270.0). Across all subgroups, Black adults had the highest hospitalization rate in 2019, and there was a significant increase in the differences in hospitalizations between Black and White people from 1999 to 2019. Marked geographic variation was also present, with the highest hospitalization rates in the South. Among patients hospitalized for acute hypertension, the observed 30-day and 90-day all-cause mortality rates (95% CI) decreased from 2.6% (2.27–2.83) and 5.6% (5.18–5.99) to 1.7% (1.53–1.80) and 3.7% (3.45–3.84) and 30-day and 90-day all-cause readmission rates decreased from 15.7% (15.1–16.4) and 29.4% (28.6–30.2) to 11.8% (11.5–12.1) and 24.0% (23.5–24.6). Conclusions: Among Medicare fee-for-service beneficiaries age 65 years or older, hospitalization rates for acute hypertension increased substantially and significantly from 1999 to 2019. Black adults had the highest hospitalization rate in 2019 across age, sex, race and ethnicity, and dual-eligible strata. There was significant national variation, with the highest rates generally in the South. Abstract : Supplemental Digital Content is available in the text.